Mixed Ligand Complexes of Alkaline Earth Metal Salts of Some Organic Acids with Isonitroso-p-methyl Acetophenone - Prakash, Dharm; Ram Prasad Singh, Jai; kumar, Birendra (Asian Journal of Chemistry, 2010)
In the present work, the authors report the complexing behaviour of isonitroso-p-methyl acetophenone with various alkaline earth metal salts of the organic acids.